Análise semiótica das peças de comunicação para prevenção de riscos de desastres das defesas civis de São Paulo e de Santa Catarina - Oliveira Junior, Nilthon Fernandes de (2016)
The mainly purpose of this research is to investigate how the production of prevention and disaster risk communication booklets, made by the civil defense of São Paulo and Santa Catarina and according to their risk and disaster reduction programs, helps the representation of the relation between the community and its risk environment;; and how the inunciator intents to cons- truct and awake the resilience culture in the enunciatee. There by, inhibiting behaviors, that can increase the community vulnerability from methodological, hydrological and geological disasters. In this context, the information and edu- cational materials, when they represent consistent behaviors with the resilien- ce culture, from the figuration process and theming of the actions and attitudes of the communities, they also become able to contribute in the vulnerability reduction of these groups and, with that, minimize the disaster impacts. Howe- ver, oftentimes, the materials are produced and spread without the concern of make them effectives as communication contracts. Therefore, this research begins with the hypothesis that the disaster risk com- munication, especially by São Paulo and Santa Catarina, only accomplishes national and International protocols. To achieve the objects of this research, it was adopted, as part of the central methodological procedure;; the discourse analysis with the discursive semio- tics of the communication pieces, added to the survey and the critical analysis of the risk and disasters communication field bibliography and its interface with the disaster risk reduction